2022
DOI: 10.1227/neu.0000000000001929
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Automated Analysis of Skull Base Tumor Specimens Using Intraoperative Optical Imaging and Artificial Intelligence

Abstract: BACKGROUND:Accurate specimen analysis of skull base tumors is essential for providing personalized surgical treatment strategies. Intraoperative specimen interpretation can be challenging because of the wide range of skull base pathologies and lack of intraoperative pathology resources.OBJECTIVE:To develop an independent and parallel intraoperative workflow that can provide rapid and accurate skull base tumor specimen analysis using label-free optical imaging and artificial intelligence.METHODS:We used a fiber… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…It was therefore chosen for further validation and analysis. Other studies showed similar overall accuracy as well as ROC-AUC ranging from approximately 84 to 97% between the CNN- and neuropathological-based SRH image analysis [ 4 , 5 , 15 , 16 ]. However, it should be noted that the CNN deployed in these studies had different output classes with different loss functions.…”
Section: Discussionmentioning
confidence: 67%
“…It was therefore chosen for further validation and analysis. Other studies showed similar overall accuracy as well as ROC-AUC ranging from approximately 84 to 97% between the CNN- and neuropathological-based SRH image analysis [ 4 , 5 , 15 , 16 ]. However, it should be noted that the CNN deployed in these studies had different output classes with different loss functions.…”
Section: Discussionmentioning
confidence: 67%
“…One application of SRH is the detection of tumor infiltration in real-time to improve the extent of tumor resection and reduce residual tumor burden. Real-time SRH-based tumor delineation has been studied in sinonasal/skull base cancers [13,29,30] and diffuse gliomas [19,31]. OpenSRH provides the necessary dataset to explore this topic for multiple brain tumor types, including metastatic tumors and extra-axial tumors, such as meningiomas (Figure 1).…”
Section: Related Workmentioning
confidence: 99%
“…Standardized: SRH image acquisition is invariant to patient demographic features, clinical workforce, and geographic location 4. Accurate: preliminary results [6,13] and diagnostic performance benchmarks (see Figure 4) are on par with the pathologist-based interpretation of H&E histology…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations